2005
DOI: 10.1021/jp0522664
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Structural Changes in the Active Site of the BLUF Domain in AppA by Raman Spectroscopy

Abstract: The flavin-adenine-dinucleotide-binding BLUF domain constitutes a new class of blue-light receptors, and the N-terminal domain of AppA is a representative of this family. AppA functions as a transcriptional antirepressor, controlling the photosynthesis gene expression in the purple bacterium Rhodobacter sphaeroides. Upon light absorption, AppA undergoes a photocycle with a signaling state, which exhibits an approximately 10 nm red shift in the UV-vis absorption spectrum. We have characterized light-dependent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
150
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(174 citation statements)
references
References 25 publications
24
150
0
Order By: Relevance
“…FTIR showed that light exposure weakens the carbonyl bonds at C2 and C4 of the flavin, but suggested much larger changes in the protein itself (21,22). Stronger hydrogen bonding between the flavin O4 atom and the neighboring glutamine residue can explain the spectral shifts (13,(21)(22)(23) and is reflected in changes at the exterior of the BLUF domain, near the last β-strand and the surface tryptophan. This change leads to different downstream effects in different proteins; for example in BlrP1, it affects the coordination of essential metal ions at the active site of the neighboring domain (7).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…FTIR showed that light exposure weakens the carbonyl bonds at C2 and C4 of the flavin, but suggested much larger changes in the protein itself (21,22). Stronger hydrogen bonding between the flavin O4 atom and the neighboring glutamine residue can explain the spectral shifts (13,(21)(22)(23) and is reflected in changes at the exterior of the BLUF domain, near the last β-strand and the surface tryptophan. This change leads to different downstream effects in different proteins; for example in BlrP1, it affects the coordination of essential metal ions at the active site of the neighboring domain (7).…”
Section: Significancementioning
confidence: 99%
“…Different BLUF proteins show very different rates of return to the dark state, which occurs within a few seconds in some cases and a few minutes in others (4,21). FTIR showed that light exposure weakens the carbonyl bonds at C2 and C4 of the flavin, but suggested much larger changes in the protein itself (21,22). Stronger hydrogen bonding between the flavin O4 atom and the neighboring glutamine residue can explain the spectral shifts (13,(21)(22)(23) and is reflected in changes at the exterior of the BLUF domain, near the last β-strand and the surface tryptophan.…”
Section: Significancementioning
confidence: 99%
“…The molecular identities of the BLUF dark and photoactivated states remain controversial as X-ray and NMR structures have given different orientations for the conserved glutamine in the dark (i.e., with the amino group hydrogen bonded to the conserved tyrosine or to FAD C 4 dO; see Figure 1A,B). A similar issue holds for W91 and M93, which were found either close to FAD or exposed to the solvent (4-8, 12, 13).The current opinion on the photoactivation of the BLUF domains as observed by steady-state FTIR (14-16), Raman (17,18),, and quantumchemical calculations (26-29) includes light-induced radical pair formation by electron and proton transfer from an essential tyrosine side chain (Y8) to the flavin cofactor on the picosecond time scale. Subsequently, hydrogen bond rearrangement takes place, possibly involving ∼180°rotation of the amide group of an essential glutamine side chain (Q50) which is followed…”
mentioning
confidence: 92%
“…In contrast, flavincontaining BLUF (blue-light using flavin adenine dinucleotide (FAD)) (2) proteins show a different photoactivation mechanism that is not accompanied by prominent structural changes in the chromophore (3). In BLUF proteins, the signaling state is characterized by a light-induced~10 nm red shift of the ultraviolet-visible (UV-vis) absorption spectrum (4-10) and an~16 cm À1 downshift of the C4¼O stretching mode of the flavin ring (11)(12)(13). These relatively minor spectroscopic changes are characteristic of BLUF proteins.…”
Section: Introductionmentioning
confidence: 99%